ANALISIS KINERJA BUNDARAN TUGU PANCASILA JL. DIPONEGORO KABUPATEN JEPARA - Yayan Adi Saputro; Khotibul Umam (Universitas PGRI Semarang, 2021)
The increase in population is always accompanied by an increase in the process of moving from one place to another. One of the engineering measures that can be done as an effort to regulate the displacement process is the existence of a roundabout. Pancasila Monument roundabout Jl. Diponegoro, Jepara Regency is one of the objects for conducting a performance review using vehicle survey methods, road inventory, and analysis. The survey results obtained that VLHR at the Tugu Pancasila Roundabout is quite dense with a capacity of up to 1,503.09 smp / hour from West-North, 1,890.40 from North-South, and 1,557.12 South-West. The level of service value of 0.88 is included in the service level category E, namely the traffic flow indicator is higher than the service level D with traffic volume approaching road capacity and very low speed. The driver began to feel the congestion with a short duration. The ratio of non-motorized vehicles to motorized vehicles was 0.015%, the ratio of left-turning vehicles was 19.790%, the ratio of right-turning vehicles was 29.867%, the ratio of PMI minor road vehicles was 50.342%.